Analysis of Soybean Demand in Klaten Regency - Arif Ludianzah; Darsono Darsono; Agustono Agustono (Central Research Institute For Agriculture, 2023)
The aims are to analyze and identify the factors that affect demand for soybeans and the level of sensitivity (elasticity) demand of soybean in Klaten Regency. The basic method used descriptive analysis. Intake of study sites in purposive in Klaten Regency. The data is analyzed secondary data (time series) during 16 years (1993-2008). Data analysis using OLS (Ordinary Least Square) with a double logarithmic function, to obtain the coefficient of elasticity that is in use in static and dynamic analysis model. Elasticity of demand for the static model based on price elasticity, demand for soybeans is inelastic. Based on the income elasticity, soy is a normal good. Whereas for a dynamic analysis model, the elasticity of demand for short-term and long term for soybean prices is inelastic with a value of -0,134 and -0,1595. This means a change of 1% soybean prices will reduce demand for soybeans -0,134% in the short term and -0,1595% in the long term. The elasticity of demand for shortterm and long-term residents for revenue is inelastic with a value of 0,094 and 0,1119. This means that changes in population income by 1% would raise soybean demand for 0.094% in the short term and 0,1119% in the long term. The elasticity of demand for short-term and long term for the total population is elastic with a value of 2,150 and 2,5595. This means that changes in population income by 1% would raise soybean demand for 2,150% in the short term and 2,5595% in the long term.